Implementation of the Regulation of the Minister of ATR/BPN No. 14 of 2024 in the Registration of Customary Land Rights of Customary Law Communities: Implementasi Peraturan Menteri ATR/BPN No. 14 Tahun 2024 dalam Pendaftaran Tanah Hak Ulayat Masyarakat Hukum Adat - Rohyani Rigen Is Sumilat (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
The implementation of Permen ATR/BPN No. 14 of 2024 represents a strategic move in the recognition of hak ulayat (communal land rights) for Indonesia’s indigenous communities. This regulation responds to the long-standing issues of complex and non-transparent registration processes that have marginalized indigenous people from formal land registration. Despite previous reforms, data from the Indonesian Land Agency (BPN) in 2022 indicates that only 30% of ulayat land has been officially registered. The aim of this study is to analyze the effectiveness of the policy, particularly in addressing challenges such as legal uncertainty, conflicts over land claims, and administrative bottlenecks. The study employs a normative juridical method with a comprehensive legal analysis of relevant regulations, including Permen ATR/BPN No. 3 of 2023 and Permen ATR/BPN No. 21 of 2020, alongside secondary data sources such as legal literature and empirical case studies on land conflicts involving indigenous communities. The analysis focuses on how the Permen ATR/BPN No. 14 of 2024 aligns with broader land management reforms and the technological innovations introduced by Permen 2023, which facilitates electronic land registration.